Bid-Price Controls for Network Revenue Management: Martingale Characterization of Optimal Bid Prices - Akan, Mustafa; Ata, Baris (Mathematics of operations research, 2009)
We consider a continuous-time, rate-based model of network revenue management. Under mild assumptions, we construct a simple -optimal bid-price control, which can be viewed as a perturbation of a bid-price control in the classical sense [Williamson, E. L. 1992. Airline network seat control. Ph.D. thesis, MIT, Cambridge, MA]. We show that the associated bid-price process forms a martingale and the corresponding booking controls converge in an appropriate sense to an optimal control as tends to 0. Moreover, we show that there exists an optimal generalized bid-price control, where the bid-price process forms a martingale and is used in conjunction with a capacity usage limit process. We also discuss its connection to the bid-price controls in the classical sense and sufficient conditions for the (near) optimality of the latter.